NO2 Absorption in Aqueous Solutions with Phenolic Additives : Hydroquinone and 4-Methylaminophenol Sulfate - Schmid Daniel; Hupa Mikko; Paavola Mikko; Karlström Oskar (American Chemical Society, 2025)
NO2 absorption has recently gained attention as a promising alternative to conventional NOx reduction methods. One key challenge in NO2 absorption is that high amounts of additives are required to maintain satisfactory absorption efficiency. The present study investigates the absorption of NO2 from flue gases in aqueous solutions with low concentrations of phenolic additives. Absorption tests with hydroquinone and 4-methylaminophenol sulfate were performed in a laboratory-scale absorption system with test gases containing 0 or 5% O2 (N2 as a balance gas) and 50, 100, or 150 ppm of NO2, representing typical flue gas conditions in a range of industrial processes. The results show that NO2 was absorbed efficiently with small concentrations of 4-methylaminophenol sulfate, both with 0 or 5% O2 in the test gas. Hydroquinone also enhanced NO2 absorption but to a lesser degree than 4-methylaminophenol sulfate. Interestingly, the presence of O2 did not influence the consumption of the phenolic additives, in contrast to commonly used additives such as sulfite that require oxidation inhibitors such as thiosulfate. With a 2 mM solution of 4-methylaminophenol sulfate, more than 90% of the incoming NO2 was absorbed. Thus, NO2 absorption with 4-methylaminopheno sulfate appears to be able to remove NOx emissions from flue gases with high efficiency.